The Australian art field
1 online resource (xix, 325 pages)
Keywords: "This book brings together leading scholars and practitioners to take stock of the frictions generated by a tumultuous time in the Australian art field and to probe what the crises might mean for the future of the arts in Australia. Specific topics include national and international art markets; art practices in the context of their broader social and political contexts; social relations and institutions and their role in contemporary Australian art; the policy regimes and funding programmes of Australian governments; and national and international art markets. In addition, the collection will pay detailed attention to the field of indigenous art and the work of indigenous artists. This book will be of interest to scholars in contemporary art, art history, Asia Pacific studies, and indigenous peoples"--